Thrills, chills, frissons, and skin orgasms: toward an integrative model of transcendent psychophysiological experiences in music - Harrison, Luke; Loui, Psyche (Frontiers in Psychology, 2014)
Music has a unique power to elicit moments of intense emotional and psychophysiological response. These moments – termed “chills,” “thrills”, “frissons,” etc. – are subjects of introspection and philosophical debate, as well as scientific study in music perception and cognition. The present article integrates the existing multidisciplinary literature in an attempt to define a comprehensive, testable, and ecologically valid model of transcendent psychophysiological moments in music.